Collaborative Management for Public Facilities and Biogas on the Village Land - Zaflis Zaim (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Tanjungpura, 2021)
A village land is an asset belonging to the village or common goods, not belonging to individuals, foundations, Institution or companies so that it must be used for the benefit of the village or the administration of government. This research identified the constraints on the use of Bengkok as a village land, exploring the format of collaborative management (co-management) in the utilization of Biogas installation and public facilities such as: composting, chopper, water tank, play group, meeting room and warehouse. The research method was taken with in-depth interview and observation to obtain the data through all member of the farmer groups, the religious and community leaders, and village government staff. The results indicated that the utilization and management of the village land by farmer groups were not yet optimal. The cow's milk production was still quite small, volatile, and tended to decline. The decreased milk production resulted in the loss of other processed products such as soap, candy and crackers from milk ingredients. Other impacts included the closing of the business opportunities for fertilizer from livestock manure, and the passive supply of household gas obtained from the biogas installation. This research initiated the need for the role of 5 stakeholders, namely Ungaran Regency government, village government, private parties, social institution, and the local communities in order to collaborate on Biogas and public facilities management. The social institutions were formed to repair or improve the Biogas management and water supply for all facilities on the village land.